Validation of the Effectiveness and Safety of Temozolomide during and after Radiotherapy for Newly Diagnosed Glioblastomas: 10-year Experience of a Single Institution - Joo, Jin-Deok; Kim, Hansol; Kim, Young-Hoon; Han, Jung Ho; Kim, Chae-Yong (Journal of Korean medical science, 2015)
This study was performed to validate the effectiveness and safety of concurrent chemoradiotherapy and adjuvant therapy with temozolomide for newly diagnosed glioblastoma multiforme as a standard treatment protocol. Between 2004 and 2011, patients newly diagnosed with glioblastoma who were treated with temozolomide during concurrent chemoradiotherapy and adjuvant chemotherapy were included from a single institution and analyzed retrospectively. The primary endpoint was overall survival, and the secondary endpoints were progression-free survival, response, and safety. A total of 71 patients were enrolled in this study. The response rate was 41% (29/71), and the tumor control rate was 80% (57/71). In the 67 patients who completed the concurrent chemoradiotherapy with temozolomide, the median overall survival was 19 months and the 1- and 2-yr overall survival rates were 78.3% and 41.7%, respectively. The median progression free survival was 9 months, and the 1- and 2-yr progression free survival rates were 33.8% and 14.3%, respectively. The mean duration of survival after progression of disease in salvage treatment group was 11.9 (1.3-53.2) months. Concurrent chemoradiotherapy with temozolomide resulted in grade 3 or 4 hematologic toxic effects in 2.8% of the patients. The current protocol of temozolomide during and after radiation therapy is both effective and safe and is still appropriate as the standard protocol for treatment of glioblastoma. An active salvage treatment might be required for a better prognosis.